Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2165/00003088-200241060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the Carmustine Implant

Abstract: Controlled release delivery of carmustine from biodegradable polymer wafers was approved as an adjunct to surgical resection in the treatment of recurrent glioblastoma multiforme after it was shown in clinical trials to be well tolerated and effective. Given the localised nature of the drug in the brain tissue, no direct pharmacokinetic measurements have been made in humans after implantation of a carmustine wafer. However, drug distribution and clearance have been extensively studied in both rodent and non-hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 56 publications
7
170
1
Order By: Relevance
“…Previous pharmacokinetic studies on animals and associated modelling demonstrated the ability of carmustine wafers to produce high-dose delivery (millimolar concentrations) within millimeters of the polymer implant, with a limited penetration distance of carmustine from the site of delivery (13). In addition, the presence of significant doses of carmustine in more distant regions of the brain (centimeters away from the carmustine wafer implant) has been shown to persist over the course of 1 week in non-human primates (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous pharmacokinetic studies on animals and associated modelling demonstrated the ability of carmustine wafers to produce high-dose delivery (millimolar concentrations) within millimeters of the polymer implant, with a limited penetration distance of carmustine from the site of delivery (13). In addition, the presence of significant doses of carmustine in more distant regions of the brain (centimeters away from the carmustine wafer implant) has been shown to persist over the course of 1 week in non-human primates (13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of significant doses of carmustine in more distant regions of the brain (centimeters away from the carmustine wafer implant) has been shown to persist over the course of 1 week in non-human primates (13). However, Fung et al (12) revealed that a significant concentration of carmustine (0.4 ”M) was detected at up to 5 cm from the implant as late as 30 days after implantation, although a high drug concentration (0.5-3.5 mM) was measured within 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Biopolymer tech-nology has allowed chemotherapeutic agents to be placed and gradually released at the brain surface subsequent to tumor resection, providing higher local concentrations than possible via systemic delivery, without the associated systemic toxicity. [15][16][17] Depending on the biopolymer composition, drugs can be delivered in a controlled manner for a finite period of time. Unfortunately, reoperation is required for re-dosing of the patient with these biopolymers, and controversy remains over cost and associated morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…During brain tumor excision, gel wafers embedded with chemotherapeutics are inserted into the space previously occupied by tumor, resulting in slow release of drug precisely in the region of persisting malignant cells (31). Ongoing studies are focused on the development of a cytochrome c mimetic that could be delivered in such a manner to eliminate brain tumor cells without harming surrounding neural tissue.…”
Section: Discussionmentioning
confidence: 99%